2018
DOI: 10.3892/ol.2018.9478
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis promotes cell apoptosis through the G protein‑coupled receptor 4/CCAAT/enhancer‑binding protein homologous protein pathway

Abstract: The aim of the present study was to investigate the effects of acidosis on the apoptosis of renal epithelial and endothelial cells, and the molecular pathways responsible for this. A human proximal tubular cell line, HK-2, and human umbilical vein endothelial cells (HUVECs), were transfected with control or G protein-coupled receptor 4 siRNA for 36 h. Cells were exposed to normal (pH 7.4) or acidic (pH 6.4) media. Western blot analysis was used to assess the protein expression levels of G protein-coupled recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…28 In addition, a recent study suggested that acidemia can promote cell apoptosis through the G protein-coupled receptor 4/ CCAAT/enhancer-binding protein homologous protein pathway. 29 A previous research demonstrated that the expression of miR-133b, which is involved in the regulation of proliferation, cell death and migration can be regulated by acidemia. 30 In the present study, the 30-day mortality and 90-day mortality of AMI patients with acidemia were higher than the AMI patients without acidemia.…”
Section: Discussionmentioning
confidence: 99%
“…28 In addition, a recent study suggested that acidemia can promote cell apoptosis through the G protein-coupled receptor 4/ CCAAT/enhancer-binding protein homologous protein pathway. 29 A previous research demonstrated that the expression of miR-133b, which is involved in the regulation of proliferation, cell death and migration can be regulated by acidemia. 30 In the present study, the 30-day mortality and 90-day mortality of AMI patients with acidemia were higher than the AMI patients without acidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of GPR4 by extracellular acidification also increase the expression of chemokines, cytokines, and adhesion molecules through the NF-kB pathway in endothelial cells (Table 1) (176)(177)(178). Acidosis-induced activation of GPR4 promotes the endoplasmic reticulum (ER) stress response and apoptosis of endothelial cells (177,179,180). GPR4 -/reduces inflammation in the DSS-induced acute colitis and in the spontaneous IL-10-/-colitis model in rodents (169,181).…”
Section: Gaq/ 11 and Gasmentioning
confidence: 99%
“…Activation of GPR4 by acidosis stimulates the expression of inflammatory chemokines, cytokines, adhesion molecules and the NF-κB pathway in endothelial cells, increases endothelium-leukocyte adhesion, and facilitates leukocyte infiltration (11)(12)(13)(14)(15)(16)20). Moreover, activation of GPR4 by acidosis promotes the endoplasmic reticulum (ER) stress response and apoptosis of endothelial cells (12,13,33).…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%